Investigating the impact of C p -T values determined by DSC on the PCM-CFD model - Iten, M. (2019)
For the numerical analysis of Phase Change Material (PCM) enable energy storage based heating/cooling technologies, thermo-physical properties of PCM are very important inputs. It is of vital significance to thermal characterise of PCM to obtain phase change temperature range and the relationship of specific heat capacity with temperature (Cp-T). This is simply done by using differential scanning calorimetry (DSC). Present paper highlights the importance of experimental heating rate in thermal characterisation of PCM. It has been observed that the heating/cooling rate plays an important factor in studying numerically the charging/discharging behaviour of a PCM. Firstly the recommended heating/cooling rate of 10 °C/min stated in ASTM D 4419 is used for the DSC, followed by the rate of 0.2 °C/min observed in the experimental testing. The phase change temperature range and the Cp-T curves have been determined for the both heating/cooling rates. An experimentally validated CFD model has been developed aiming to predict the thermal performance of PCM and the air outlet temperatures. The effective heat capacity method is applied including the Cp-T obtained from the DSC for both rates. Similar heating rate, as per experimental testing, established significant improvements in the validation results when applied in a CFD model.